2017
DOI: 10.1097/qad.0000000000001504
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of nonalcoholic fatty liver disease in HIV-monoinfection

Abstract: NAFLD is frequently observed in HIV-monoinfected patients, and NASH is a common cause of unexplained abnormal liver function in patients selected for liver biopsy. Metabolic disorders are key risk factors independently of HIV parameters. Future trials on pharmacological interventions in NASH with fibrosis should include patients with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
208
4
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(236 citation statements)
references
References 27 publications
19
208
4
5
Order By: Relevance
“…In addition, many studies report data on liver health among HIV populations with significant exposure to ART. (5,8,14,22,28,30,31) Most studies have identified traditional risk factors for abnormal liver enzymes in patients with HIV mono-infection such as metabolic syndrome (7,32) and some have found an association with HIV-related factors such as increased HIV viral load and exposure to certain antiretrovirals. (8,33) While the APRI and FIB-4 were not always in agreement, our baseline analysis identified key variables known to be associated with an increased risk of liver fibrosis, including older age, male gender, black race, abnormal ALT, co-infection with hepatitis and a history of known liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, many studies report data on liver health among HIV populations with significant exposure to ART. (5,8,14,22,28,30,31) Most studies have identified traditional risk factors for abnormal liver enzymes in patients with HIV mono-infection such as metabolic syndrome (7,32) and some have found an association with HIV-related factors such as increased HIV viral load and exposure to certain antiretrovirals. (8,33) While the APRI and FIB-4 were not always in agreement, our baseline analysis identified key variables known to be associated with an increased risk of liver fibrosis, including older age, male gender, black race, abnormal ALT, co-infection with hepatitis and a history of known liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Liver disease remains a major cause of morbidity and mortality in human immunodeficiency virus (HIV)‐infected individuals globally and is highest among those with concurrent alcohol use and/or hepatitis B and C virus coinfection . However, nonalcoholic fatty liver disease (NAFLD), which is frequently associated with metabolic syndrome, has an increased prevalence among HIV‐monoinfected individuals as well . While NAFLD most commonly causes simple steatosis, it can also progress to nonalcoholic steatohepatitis, fibrosis, and/or cirrhosis .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in the absence of viral hepatitis, liver injury caused by alcohol and nonalcoholic fatty liver disease (NAFLD) is common and may be more severe in PLWH . Indeed, NAFLD has been reported in up to 35% of PLWH and is expected to become the leading cause of cirrhosis in this population . Emerging data suggest that alterations in the gut microbiome, a diverse microbial community residing in the gastrointestinal tract, may play a key role in chronic liver disease progression in PLWH.…”
mentioning
confidence: 99%
“…
upon-Tyne, UKSir, Nonalcoholic fatty liver disease (NAFLD) is common in people living with HIV (PLWH) [1]. A recent update to European guidance suggests screening for NAFLD in PLWH who also have metabolic syndrome (MetS) [2].
…”
mentioning
confidence: 99%